The state of the cellular link of innate immunity in men depending on type and amount of alcohol consumed - Kozachuk, O. S.; Vorontsova, L. L.; Kovalenko, V. A. (Modern medical technology, 2023)
The aim. Study of the state of the cellular link of nonspecific immunity depending on the type and amount of alcohol consumed. Materials and methods. 110 men between the ages of 20 and 55 were examined, who were divided into 3 groups. The first (control) group consisted of 17 fertile men who do not drink alcoholic beverages. The second group (comparison) consisted of 27 patients who use, but do not abuse, all types of alcoholic beverages (1-2 doses of alcohol approximately once every 1-3 months). The third group consisted of 66 patients who abuse alcoholic beverages (6 or more units of alcohol at a time or 22 or more doses per week). Depending on the type of alcohol, this group was divided into 3 subgroups: 3a subgroup – 13 patients who abuse strong alcoholic beverages; 3b - 27 patients who abuse beer and 3c group - 26 patients who abuse beer and strong alcoholic beverages. All men underwent a survey to assess alcohol consumption during the past year, as well as an assessment of the phagocytic activity of the neutrophilic and monocyte units of the immune system with the calculation of the degree of immune system disorders. The results of the conducted studies showed that incomplete phagocytosis of neutrophilic and monocyte links was observed in all studied groups with preservation of the functional-metabolic reserve in groups 2 and 3a and its depletion in groups 3b and 3c. The most immunologically compromised were groups 3b and 3c, in which 1-2 degree deficiency was observed, which perhaps reflects the negative effect of beer itself on the cellular factors of innate immunity. Conclusion. Consumption of both strong alcoholic beverages and beer causes suppression of the phagocytic activity of neutrophils and stimulation of the absorption capacity of monocytes, which is manifested by ineffective phagocytosis. With the consumption of strong alcoholic beverages, preservation of the functional and metabolic reserve of neutrophils is observed, and with the consumption of beer and mixed alcoholic beverages, its deficiency is observed.